Antenatal Midwifery Care In Ny. “A” G4P0A0 With Chorionic Energy Deficiency (CED) In Sorawolio Health Center - Jusmiyati, Wa; Anita; Nurul Mutia, Wa Ode (International Journal of Multidisciplinary Learners, 2024)
Background: Chronic Energy Deficiency (CED), a condition of malnutrition where the mother suffers from long-term food deficiency resulting in health disorders, is one of the main contributing factors. CED is caused by various factors including economic problems, lack of nutritional knowledge, insufficient food production, having too many children, and an imbalance between energy intake and expenditure. Objective: can carry out antenatal midwifery care for people with chronic energy deficiency (KEK) Ny. A G4P3A0 at Puskemas Sorawolio kota Baubau in 2024. Subject: The subject of this research was 1 person, namely mother A who suffered from CED. Methods: This study employs the 7 Steps of Varney and SOAP. Results: This case study reveals the gaps or alignments between theory and practice in Antenatal Care (ANC) Midwifery Services. The research results show that Mrs. A, G4P3A0 with CED at Sorawolio Public Health Center in Baubau City was confirmed through measurements of Mid-Upper Arm Circumference (MUAC) of 22.3 cm, weight, and blood pressure. Conclusion: Ante Natal midwifery care for Ny. A has been carried out according to midwifery sevice standards.